State Land Assets Legal Protection of Indonesian Railroad System Based on Grondkaart in Semarang City - Listyowati Sumanto; Irene Eka Sihombing; Endang Pandamdari (International Journal of Social Service and Research, 2022)
State land assets owned by PT. KAI (Persero) which is controlled by another party without the permission of PT. KAI (Persero) needs attention, because most of its ownership is marked with Grondkaart, which is a map of land during the Dutch colonial era. This paper aims to analyze the issue of how the position of Grondkaart in the legislation, how the legal protection of land assets of the Indonesian railways based Grondkaart in Semarang City. Based on the decisions of the judiciary, it was found that the court's decision gave rights to PT KAI (Persero) with the consideration that Grondkaart was recognized as proof of land ownership of PT KAI (Persero), although according to the National Land Law the certificate was strong evidence. PT KAI (Persero) obtains legal protection for the land it owns, because the land has been registered as a State asset, and Grondkaart is recognized as the basis for land ownership rights. However, by pointing out Grondkaart, PT. KAI (Persero) does not necessarily obtain legal certainty of land ownership, so that in practice PT. KAI (Persero) must go to court to fight for the ownership of the land. Recommendations for PT KAI (Persero) (1) To strengthen the position of PT KAI (Persero) on unregistered land, it is necessary to build a network system between PT KAI (Persero), the Ministry of Finance of the Republic of Indonesia, and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. Thus, it can be seen that the lands of PT KAI (Persero) as state assets are based on Grondkaart. (2) As a form of effort to save state-owned assets controlled by unauthorized parties and to create legal certainty, PT KAI (Persero) must be certified with Grondkaart ground.